InχGa1-χAs on (100) InP substrate optoelectronic devices via molecular beam epitaxy - Podpod, Arnita C.
"Molecular Beam Epitaxy was used to deposit InχGa₁₋χAs layers and PN optoelectronic devices on (100) InP substrate in the interest of extending the wavelength operation of existing GaAs-based optoelectronic devices. InχGa₁₋χAs/InP system is capable of detection or emission at higher wavelength particularly at low loss and low dispersion wavelength for fiber optic communication which GaAs-based materials cannot deliver. Tensile strained InχGa1-χAs/InP PN optoelectronic detector grown at 500°C has an In mole fraction x=0.45. It has a lattice constant a=5.8372Å with resulting strain of -5.1x10⁻³. This device is capable for 1.3μm wavelength detection as exhibited from photocurrent spectrum. From SEM and in situ monitoring via RHEED its surface is covered with step-like-hump, exhibiting rough morphology. Compressive strained InχGa₁₋χAs/InP devices grown at lower substrate temperature of 420°C has an In mole fraction x=0.7Å, lattice constant a=5.937Å and strain value of 11x10³. PC measurement shows a 1.9μm wavelength onset and is sensitive to 1.5μm detection. Its surface is relatively smoother compared to device grown at 500°C substrate temperature."